Incarcerated Mothers’ Labor Market Outcomes - Jung, Haeil (The prison journal, 2017)
This study investigates how motherhood and foster care records of their children influence women’s transitions into the labor market after incarceration. Our fixed effects models examine the relative progress of incarcerated mothers in earnings and employment after incarceration, accounting for the difference between mothers and women without children and controlling for time-constant individual characteristics. Our analysis indicates that incarcerated mothers make impressive progress in quarterly employment during the second and third year after incarceration. Most of these increases are from mothers whose children started, but did not resolve, foster care before incarceration.